Substrate Mapping and Ablation for Ventricular Tachycardia: The LAVA Approach. (2nd December 2014) - SACHER, FREDERIC; LIM, HAN S.; DERVAL, NICOLAS; DENIS, ARNAUD; BERTE, BENJAMIN; YAMASHITA, SEIGO; HOCINI, MÉLÈZE; HAISSAGUERRE, MICHEL; JAÏS, PIERRE
Substrate Mapping and Ablation: Introduction: Catheter ablation of ventricular tachycardia (VT) is proven effective therapy particularly in patients with frequent defibrillator shocks. However, the optimal endpoint for VT ablation has been debated and additional endpoints have been proposed. At the same time, ablation strategies aiming at homogenizing the substrate of scar‐related VT have been reported. Methods and Results: Our method to homogenize the substrate consists of local abnormal ventricular activity (LAVA) elimination. LAVA are high‐frequency sharp signals that represent near‐field signals of slowly conducting tissue and hence potential VT isthmuses. Pacing maneuvers are sometimes required to differentiate them from far‐field signals. Delayed enhancement on cardiac MRI and/or wall thinning on multidetector computed tomography are also extremely helpful to identify the areas of interest during ablation. A strategy aiming at careful LAVA mapping, ablation, and elimination is feasible and can be achieved in about 70% of patients with scar‐related VT. Complete LAVA elimination is associated with a better outcome when compared to LAVA persistence even when VT is rendered noninducible. Conclusion: This is a simple approach, with a clear endpoint and the ability to ablate in sinus rhythm. This strategy significantly benefits from high‐definition imaging, mapping, and epicardial access.